Screening aging related proteins in urine from healthy adults - ZHENG Shu-xin, ZHAO Min-di, SHAO Chen, SUN Hai-dan, LIU Xiao-yan, GUO Zheng-guang, SUN Wei (Jichu yixue yu linchuang, 2021)
Objective To screen the differential proteins related to aging in human urine and to find out the functional changes of proteins related to aging. Methods Fourteen healthy men and 15 healthy women were enrolled and divided them into three groups according to their ages (20-30, 40-50 and over 60 years old). The differential proteins were screened by label-free quantification and 2DLC-MS/MS. Results In male group, there were 100 proteins differentially expressed in three groups, 66 were over-expressed and 34 were under-expressed. In female group, there were 94 proteins differentially expressed in three groups, 79 were overexpressed and 15 were under-expressed. There were 12 differential expressed proteins related to aging in both male and female groups. These protein pathways mainly focused on coagulation system, protein ubiquitination pathway, LXR/RXR activation and lactose degradation III, etc. Conclusions Proteins related to aging can be found in urine, which may be used as biomarkers of aging and providing basis for subsequent discovery of disease biomarkers.